Redescription of the Chilean angel shark Squatina armata (Philippi, 1887) (Squatiniformes, Squatinidae) - Kraft, Sebastián; Fernández-Cisternas, Ítalo; Araya, Miguel; Concha, Francisco J. (European Journal of Taxonomy, 2024)
Angel sharks (Squatina spp. Duméril, 1805) are a group of coastal benthic sharks distributed worldwide, currently including threatened and understudied species. Two species are formally described along the East Pacific coast, the California angel shark S. californica Ayres, 1859 and the Chilean angel shark S. armata (Philippi, 1887). The latter species occurs in the southeastern Pacific and has historically been understudied. Additionally, the original description of S. armata lacks sufficient data to confidently identify individuals of this species compared to modern descriptions, and no type specimen is currently available to ensure specimen identification. Detailed morphological descriptions for identifying species are an essential resource for solving taxonomic issues in groups of morphologically similar species and to promote the conservation of critically endangered species. Therefore, a neotype from the type locality is here designated for S. armata, and a detailed and standardized morphological characterization based on modern taxonomic works is provided. This work contributes in improving the knowledge on the Chilean angel shark taxonomy and provides an improved frame of reference for identifying angel sharks in the East Pacific, especially in areas where species may occur in sympatry.